Comparison of clusters produced from Sb2Se3 homemade polycrystalline material, thin films and commercial polycrystalline bulk using laser desorption ionisation with time of flight quadrupole ion trap mass spectrometry - Huang, F.; Prokeš, L.; Němec, Petr; Nazabal, Virginie; Havel, J. (Springer, 2019)
Comparison of clusters produced from Sb2Se3 homemade polycrystalline material, thin films and commercial polycrystalline bulk using laser desorption ionisation with time of flight quadrupole ion trap mass spectrometry was performed.
Porovnání klastrů produkovaných z doma připraveného polykrystalického materiálu Sb2Se3, tenkých vrstev a komerčního polykrystalického objemového vzorku za použití time-of-flight hmotnostní spektrometrie s desorpční ionizací laserem a kvadrupólovou iontovou pastí
Keywords: Sb2Se3; mass spectrometry; clusters; Sb2Se3; hmotnostní spektrometrie; klastry